Earthquakes and crustal structure of Himalaya from Himalayan Nepal-Tibet seismic experiment (HIMNT) - Sheehan, Anne F.; la Torre, Thomas de; Monsalve, Gaspar; Schulte-Pelkum, Vera; Bilham, Roger; Blume, Frederick; Bendick, Rebecca; Wu, Francis; Pandey, M. R.; Sapkota, S.; Rajaure, S. (Journal of Nepal Geological Society, 2008)
The Himalayan Nepal - Tibet PASSCAL Seismic Experiment (HIMNT) included the deployment of 28 broadband seismometers throughout eastern Nepal and southern Tibet in 2001- 2002. The main goals of the project were to better understand the mountain building processes of this region through studies of seismicity and Earth structure determined from local and teleseismic earthquakes. The seismic deployment was in collaboration with the National Seismological Centre, Department of Mines and Geology, Nepal, and the Institute of Geology and Geophysics of the Chinese Academy of Sciences. Our new subsurface images from HIMNT teleseismic receiver functions and local earthquake tomography show evidence of the basal decollement of the Himalaya (Main Himalayan Thrust, MHT) and an increase in Moho depth from - 45 km beneath Nepal to -75 km beneath Tibet. We find strong seismic anisotropy above the decollement, likely developed in response to shear on the MHT. The shear may be taken up as slip in great earthquakes at shallower depths. Many local earthquakes were recorded during the deployment, and the large contrast in crustal thickness and velocity structure over a small lateral distance makes the use of a 3D velocity model important to determine accurate hypocentres. Large north-south variations are found in P and S wave velocity structure across the array. High Pn velocities are found beneath southern Tibet. Seismicity shows strong alignment of shallow (15-25 km depth) events beneath the region of highest relief along the Himalayan Front, and a cluster of upper mantle earthquakes beneath southern Tibet (70-90 km depth). Weak-mantle models do not expect the upper mantle earthquakes. Focal mechanisms of these upper mantle earthquakes beneath southern Tibet are mostly strike-slip, markedly different from the norm al faulting mechanisms observed for earthquakes in the mid and upper crust beneath Tibet. This change in the orientation of the major horizontal compression axis from vertical in the upper crust to horizontal in the upper mantle suggests a transition from deformation driven by body forces in the crust to plate boundary forces in the upper mantle. Several lines of evidence point to a decoupling zone in the Tibetan mid or lower crust, which may be related to the presence of a previously suggested flow channel in the Tibetan mid crust.